Ring of bright water : a trilogy - Maxwell, Gavin, 1914-1969 (Nonpareil book, 2011)
This volume weaves together the Scottish otter stories from Maxwell's three non-fiction books, published in the 1960s, and the basis of the 1969 motion picture. While touring the Iraqi marshes, Maxwell was captivated by an otter and became a devoted advocate of and spokesman for the species. He moved to a remote house in the Scottish highlands, co-habiting there with three otters and living an idyllic and isolated life.